Optimal pricing of primary commodities in developing countries: A model from sub-Saharan Africa - Ehui, Simeon K. (IAEA, 1997)
In most developing countries, especially in sub-Saharan Africa, prices received by farmers are not optimal in the sense that they do not optimize government revenues. In this paper a dynamic model for optimal pricing of primary commodities is developed. The model and results demonstrate that optimal prices depend on marginal cost of the commodity stock, the exporting country's supply elasticity, the importing country's demand elasticity, the social rate of time discount. Therefore when the model is cast in a static framework, or the foreign elasticity of demand is not accounted for, the result could be biased.